Ultrasound Technology Parameters: Effects on Phenolics in Olive Paste and Oil in Relation to Enzymatic Activity. Issue 5 (4th April 2019) - Yahyaoui, Amira; Rigane, Ghayth; Mnif, Sami; Salem, Ridha Ben; Acar, Ayşenur; Arslan, Derya
Abstract : In this paper, the occurrence of secoiridoid aglycones via degradation of phenolic glucosides which have strong effects on commercial, nutritional, and sensory properties of olive oil is studied. The experiment consists in the sonication treatment of Chemlali and Memecik cv s. olive paste three times for 4, 8, and 10 min. This kind of approach has never been used in determining the partition and degradation of phenolics during extraction. Concerning phenolic content present in Chemlali olive oil extracted from whole olives, no significant differences are found after 10 min of treatment using ultrasound apparatus, whereas a rise of more than 60% is detected if olive paste without stones is used. On the other hand, the total phenolic content of Memecik cv . increases positively with the increasing time of treatment. Throughout this report, it is noted that enzymatic activities are affected by ultrasound treatment. Practical Applications : The results of this study will be useful in modification of present processes or development of new processes with the aim of protecting and improving the phenolic composition of olive oil. To the best of the authors' knowledge, this kind of systematic approach has never been used in determining the partition and degradation of phenolics during extraction. It is believed that describing the effects of high‐power ultrasound applications on olive paste before malaxation will exhibit possible benefits for the future of olive processing technology. The optimization of olive oil extraction parameters with proper adjustments in such a way that the quality of the product is highly increased is an important issue. The effect of ultrasound technology parameters is investigated from the point of phenolic compounds by searching their relation to enzymes in Chemlali and Memecik cvs . olive paste. In addition, the effects of stone removal during extraction are also studied in terms of enzymes in Chemlali and Memecik cvs . olive paste and phenols in olive oil. Abstract : The effect of ultrasound technology parameters is investigated from the point of phenolic compounds by searching their relation to enzymes in Chemlali and Memecik cvs . olive paste. In addition, the effects of stone removal during extraction are also studied in terms of enzymes in Chemlali and Memecik cvs . olive paste and phenols in olive oil.